The Impression of Kiai's Leadership in Managing Islamic Boarding Schools - Mukhtar Mukhtar; Minnah el-Widdah; Muhamad Padli (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
This study examined the leadership of the Kiai in the management of human resource in Islamic boarding schools in Jambi Province. This research used a descriptive analytical-qualitatives approach. Data collection was done by observation, interview, and documentation techniques. Data analysis used an interactive analysis model Miles and Huberman. Data reliability using participation extension techniques, observation accuracy, data triangulation, and consultation of promoters and promoters. Results of the study of the leadership of the Kiai in managing the boarding school human resources in Jambi Province was carried out by realizing the vision into action and work programs, receiving the right personnel in each position, even though it often collided with familiarity and limited compensation; carry out communication and coordination; and the leadership of the Kiai has not been able to manage the boarding school effectively due to weak management knowledge and synergy in realizing the vision.